Pelaksanaan Pembelajaran Teknik Vokal Di Kelas VII-3 SMP Negeri 12 Sijunjung - Shilvi Yunita; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2020)
The purpose of this study is to describe and find out the implementation of vocal Technique learning at class VII-3 in SMP Negeri 12 Sijunjung. This type of study was a qualitative research with using descriptive methods. The object of this study was the students at class VII-3 in SMP N 12 Sijunjung who participated in vocal technique learning. The main instrument in this study was the researcher. The additional instruments were stationery and camera. Techniques of Data collection were carried out by taking literature study, observation, interviews, documentation study. The type of data used primary and secondary data. The steps in analyzing data were done by collecting, reducting, presentating and drawing data conclusions. The result shows that the vocal technique learning thatis carried out by the teacher atclass VII-3 does not run well and meet the target of the learning objectives. The teacher does not understand the material of vocal technique well so that the students do not understand the vocal technique. Therefore, there are still some students who have not been able to sing properly due to lack of practice, lack of understanding of the material and practice of vocal technique learning so that they get a low scores. The results of the practice of various vocal techniques namely the highest value only reaches 87 and the lowest value is 58 with an average value is 74.4%.